2005
DOI: 10.1038/nm1277
|View full text |Cite
|
Sign up to set email alerts
|

An astrocytic basis of epilepsy

Abstract: Hypersynchronous neuronal firing is a hallmark of epilepsy, but the mechanisms underlying simultaneous activation of multiple neurons remains unknown. Epileptic discharges are in part initiated by a local depolarization shift that drives groups of neurons into synchronous bursting. In an attempt to define the cellular basis for hypersynchronous bursting activity, we studied the occurrence of paroxysmal depolarization shifts after suppressing synaptic activity by TTX and voltage-gated Ca 2+ channel blockers. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
639
5
12

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 742 publications
(690 citation statements)
references
References 45 publications
26
639
5
12
Order By: Relevance
“…Thus, enhanced or reduced gliotransmission might directly translate into neurological disease. Recently, it was demonstrated that prolonged episodes of neuronal depolarization evoked by astrocytic release of glutamate contributed to epileptiform discharges (Tian et al, 2005). This study provided support for the concept that astrocytes are involved in the initiation, maintenance and spread of seizures.…”
Section: Astrogliosissupporting
confidence: 61%
See 1 more Smart Citation
“…Thus, enhanced or reduced gliotransmission might directly translate into neurological disease. Recently, it was demonstrated that prolonged episodes of neuronal depolarization evoked by astrocytic release of glutamate contributed to epileptiform discharges (Tian et al, 2005). This study provided support for the concept that astrocytes are involved in the initiation, maintenance and spread of seizures.…”
Section: Astrogliosissupporting
confidence: 61%
“…This is also true for newer antiepileptic drugs, such as gabapentin and pregabalin, which have recently been demonstrated to act on the α 2 -δ subunit of a voltagegated calcium channel, thus attenuating the calcium flux into neurons (Davies et al, 2007;Field et al, 2007;Taylor et al, 2007). Apart from dysfunction of neuronal networks (Holmes and Ben-Ari, 2003), dysfunction of astrocytes has recently emerged as a critical component of epileptogenesis adding an additional layer of complexity to the underlying disease process (Borges et al, 2006;Tian et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence implicating astrocytes in the generation of epileptic activity suggest that selective targeting of astrocytic gap junctions, such as Cx43, may be a fruitful strategy. 418 The novel benzoylamino benzopyran tonabersat [SB-220453; an analog of the anticonvulsant carabersat (SB-204269) 419 ], which is currently in clinical development for migraine, is believed to block gap junctions. 420 …”
Section: Gap Junctions (Connexins)mentioning
confidence: 99%
“…The involvement of astrocytes in the pathogenesis of epileptogenesis is based on findings that astrocytes control synaptic transmission by the vesicular release of glutamate, ATP, and by the release of the NMDA receptor co-agonist D-serine (Haydon and Carmignoto, 2006). Recently, it was demonstrated that prolonged episodes of neuronal depolarization evoked by astrocytic release of glutamate contributed to epileptiform discharges (Tian et al, 2005). Thus, astrocyte dysfunction appears to be a major contributing factor to epileptogenesis.…”
Section: Introductionmentioning
confidence: 99%